Systematic review on prevalence of ADHD, possible ADHD or ADHD symptoms in medical students - Lee, Nicholas Yew Wen; Zhang, Melvyn Wei Bin (Frontiers in Psychiatry, 2025)
IntroductionAttention-Deficit/Hyperactivity Disorder (ADHD) is a persistent neurodevelopmental disorder that often continues into adulthood, with a global adult prevalence of approximately 3.1%. Among medical students, the condition may be particularly underdiagnosed and undertreated, despite the intense cognitive, emotional, and psychological demands of medical education. This systematic review aimed to examine the prevalence of ADHD in medical students across diverse settings.MethodsA comprehensive literature search was conducted in September 2024 across seven major databases, yielding 499 articles.ResultsAfter de-duplication and applying inclusion criteria, 29 studies from 17 countries were included, encompassing 24,578 medical students. Reported prevalence rates ranged widely from 1.7% (self-report) to 38.9% (ASRS screener), with substantial variation across countries and even within the same regions. The most commonly used diagnostic instrument was the World Health Organization Adult ADHD Self-Report Scale (ASRS), though studies used different cutoffs and subscales. Other methods included the Wender Utah Rating Scale, structured clinical interviews, and self-report measures. Studies relying on self-report tended to show lower prevalence rates compared to those using structured tools.DiscussionHigher prevalence rates suggest that the stressors of medical education may amplify ADHD symptoms or that these environments attract or select for individuals with such traits. Despite the significant prevalence and associated functional impairments, there remains a lack of structured support systems for affected students. Early identification of ADHD in medical training could allow for tailored interventions, improved academic performance, reduced burnout, and better long-term outcomes. Additionally, the under-recognition of ADHD in medical students may have downstream effects on patient care if symptoms persist into clinical practice. This review underscores the need for standardized diagnostic criteria, structured assessments, and greater institutional support to address the challenges posed by ADHD in medical education. Further research should explore longitudinal outcomes, treatment efficacy, and the development of comprehensive support strategies for medical students with ADHD.